Faktor-Faktor yang Mempengaruhi Kinerja Karyawan Pabrik Pengolahan Kelapa Sawit PT. Tani Prima Makmur Kabupaten Konawe - Tauwi Tauwi (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2024)
The purpose of this study was to analyze the factors that affect employee performance at the PT. Tani Prima Makmur Palm Oil Mill. Based on this study because the population is not greater than the respondents, the author took 100% of the population at the PT. Tani Prima Makmur Palm Oil Mill, Konawe Regency, which was 83 respondents. This study uses multiple linear analysis to obtain a comprehensive picture of the work environment variables (x1), work pressure (x2), and social support (x3) on employee performance (y). The Work Environment partially has a negative and insignificant effect on Employee Performance at the PT. Tani Prima Makmur Palm Oil Mill, namely 0.615> 0.05. Work Pressure partially has a positive and significant effect on Employee Performance at PT. Tani Prima Makmur, namely 0.000 <0.05. Social Support has a positive and significant effect on Employee Performance at PT. Tani Prima Makmur, Konawe Regency, namely 0.000 <0.05.